Institutionalising ethics in Malaysian corporate governance - Abdul Rahman, Rashidah; Othman, Zaleha; Puteh Salin, Ahmad Saiful Azlan (2011)
This research examine the institutionalization of ethics incorporated in the public listed companies in order to instigate whether incorporations of ethics structure would influence the governance practices. The literature has shown that there is an increase in integrating values, specifically ethics, in corporate governance. At the same time, the literature also indicate there is lack of attempt made by academia to examine the possibility of integrating ethics in corporate governance. Taken the above lacuna into account, the researchers indulge to examine the institutionalisation of ethics that stimulate corporate governance practices. In doing so, the researchers employ triangulation method, where quantitative method is supported by qualitative method. The study found several interesting ethics structures that have been integrated to stimulate corporate governance practices. Analysis of the quantitative data indicate implicit and explicit ethics structure guide and direct corporate governance practices. The triangulation findings of this study indicate congruency with the literature, where it is confirmed that a formal ethical structure establishes a strategy for good practices. There is also empirical support that indicate implicit ethics structure have more influence on corporate governance practices than explicit ethics. Such findings is also validated in the research data, where descriptive analysis indicate more than 40 percent of the respondents perceived implicit ethics influence corporate governance. Comparatively, qualitative findings revealed three themes of ethical structure emerged; implicit, explicit and external. There is common understanding between both findings (quantitative and qualitative findings) that the respondents agreed the ethical structures influenced corporate governance practices. Implicit ethics commonly emerged in the shape of policy and device. Explicit ethics structure on the other hand, comprise of ethics policy and ethics instruments. The findings of this research are useful for three main groups: academics, practitioners and regulators. In regards to academia, the mix method employed for this research introduced new paradigm of method used to investigate corporate governance, where survey commonly used as method adopted. This research contributes to practitioners and regulators in several ways. The development of the ethics dimensions, that are implicit, explicit and external ethics structure validated the possibility of implementing new guidelines, rules or regulations in order to improve the present governance system. In addition, the pragmatic approach employed directs the corporate reality to the world of values, hence, indicating that managerial implications would result in the incorporation of an ethical foundation in the system.